Policy Makers, Advisors, and Reputation - Phongthorn Wrasai; Otto H. Swank (Tinbergen Institute, 2004)
When hiring an adviser (he), a policy maker (she) often faces the problem that she has incomplete information about his preferences. Some advisers are good, in the sense that their preferences are closely aligned to the policy maker's preferences, and some advisers are bad. Recently, some scholars have argued that the policy maker's power to replace her adviser induces the adviser to act more in line with the policy maker's interests. The idea is that the adviser's desire to put a stamp on future policy reduces his incentive to manipulate information. This paper shows that the policy maker's power to replace her adviser may harm her. The reason is that this power may have an adverse effect on the behavior of good advisers.
Keywords: D78; D82; D83; 330; Reputation; Signalling; Uncertainty; Policy decision-making; Politikberatung; Reputation; Politische Entscheidung